2020
DOI: 10.3389/fimmu.2020.01279
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Chimeric Construct Comprising a Modified Bacterial Superantigen and a Cruzipain Domain Confers Protection Against Trypanosoma cruzi Infection

Abstract: Chagas disease is an endemic chronic parasitosis in Latin America affecting more than 7 million people. Around 100 million people are currently at risk of acquiring the infection; however, no effective vaccine has been developed yet. Trypanosoma cruzi is the etiological agent of this parasitosis and as an intracellular protozoan it can reside within different tissues, mainly muscle cells, evading host immunity and allowing progression towards the chronic stage of the disease. Considering this intracellular par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…These studies have also confirmed the central role of IFNγ and the activation of CD4 + and CD8 + T cells in mediating parasite control, and a balanced Th1/Th2 response seems to provide a better outcome compared with a hyperpolarized response ( Table 1 ). Additional specific subpopulations of immune cells are also emerging as complementary contributors that can mediate parasite elimination, including Th17 and NK cells, as well as trypanolytic/neutralizing antibodies [ 53 , 59 , 60 , 61 , 65 ]. While the confirmation of earlier results is encouraging, a major limitation of these approaches is that they remain limited in the breadth of the immune response assessed.…”
Section: Current Vaccine Platformsmentioning
confidence: 99%
“…These studies have also confirmed the central role of IFNγ and the activation of CD4 + and CD8 + T cells in mediating parasite control, and a balanced Th1/Th2 response seems to provide a better outcome compared with a hyperpolarized response ( Table 1 ). Additional specific subpopulations of immune cells are also emerging as complementary contributors that can mediate parasite elimination, including Th17 and NK cells, as well as trypanolytic/neutralizing antibodies [ 53 , 59 , 60 , 61 , 65 ]. While the confirmation of earlier results is encouraging, a major limitation of these approaches is that they remain limited in the breadth of the immune response assessed.…”
Section: Current Vaccine Platformsmentioning
confidence: 99%